Syntactic and Semantic Analysis of Word “Over” In Gabriel Garcia Marquez’s Novel “One Hundred Years of Solitude” - Rina Mutiarawati; Ami Nur Najmillah; Zubaedah Wiji Lestari (UNIB Press, 2022)
The aim of this study is to analyze the meaning of the word “over” through syntactic and semantic analysis based on its structure. Moreover, this study also evaluates the features of the word “over” based on the structure whether they are used as an adverb, an adjective, a preposition, or a phrasal verb. This research employs qualitative descriptive research where the data are taken from the novel “One Hundred Years of Solitude” by Gabriel Garcia Marquez. As a result of data analysis, the researchers found that word over not only functions as a pure preposition, but also as an adverb, an adjective, and a phrasal verb. It can be seen from the position and function of the word “over” in a sentence. In semantic analysis, the particle “over” is analyzed as a pure preposition, an adverb, an adjective, and a phrasal verb based on the definition of “over” from two well-known dictionaries. Hopefully, the study result can be beneficial theoretically and practically for teachers or future researchers who were passionate about analyzing words from a syntactic and semantic point of view.